2021
DOI: 10.3389/fmicb.2021.717727
|View full text |Cite
|
Sign up to set email alerts
|

Low Crude Protein Diet Affects the Intestinal Microbiome and Metabolome Differently in Barrows and Gilts

Abstract: Low protein diets are commonly used in the growing-finishing pig stage of swine production; however, the effects of low dietary protein on the intestinal microbiota and their metabolites, and their association with pig sex, remain unclear. The present study aimed to assess the impact of a low crude protein (CP) diet on the gut microbiome and metabolome, and to reveal any relationship with sex. Barrows and gilts (both n = 24; initial body = 68.33 ± 0.881 kg) were allocated into two treatments according to sex. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…Our results strongly suggest that low CP diet could reduce beneficial gut microbiome metabolites, but the addition of probiotics could restore metabolite production by the gut commensals in low CP diet. Moreover, we observed that reduction in dietary CP level also influenced the function of the gut microbiome, which is consistent with the results of previous studies (Liu et al, 2021;Tao et al, 2021). Pathways related to amino acid metabolism were enriched in the LP-P and NP-P groups compared with the NP or LP groups.…”
Section: Discussionsupporting
confidence: 92%
“…Our results strongly suggest that low CP diet could reduce beneficial gut microbiome metabolites, but the addition of probiotics could restore metabolite production by the gut commensals in low CP diet. Moreover, we observed that reduction in dietary CP level also influenced the function of the gut microbiome, which is consistent with the results of previous studies (Liu et al, 2021;Tao et al, 2021). Pathways related to amino acid metabolism were enriched in the LP-P and NP-P groups compared with the NP or LP groups.…”
Section: Discussionsupporting
confidence: 92%
“…By these results, we also found that the LP diet induced a significant decrease of Lactobacillus abundance in the ileal digesta of finishing pigs compared to the HP diet in the present study. Similarly, a recent study also showed that the LP diet increased intestinal microbiota species and richness indices in both barrows and gilts, and the relative abundances of unidentified Clostridiales, Neisseria , unidentified Prevotellaceae , and Gracilibacteria at genus level were significantly affected by dietary CP levels ( 50 ). Consistently, we found that the LP diet significantly affected the diversity index of microbiota in the ileal digesta of finishing pigs.…”
Section: Discussionmentioning
confidence: 82%
“…In addition to the intestinal tract, metabolites can also be affected by sex, and a lower CP content in the diet has a greater impact on sow metabolism ( Tao et al, 2021 ). However, no differential metabolic pathways were detected in the jejunum and ileum of pigs when the pigs were feeding a diet containing 20% CP compared to the pigs fed a diet containing 22% CP in the present study, possibly because of their small differences in protein content.…”
Section: Discussionmentioning
confidence: 99%